Changes in Renal Anatomy After Fenestrated Endovascular Aneurysm Repair. (January 2017) - Maurel, B.; Lounes, Y.; Amako, M.; Fabre, D.; Hertault, A.; Sobocinski, J.; Spear, R.; Azzaoui, R.; Mastracci, T.M.; Haulon, S.
Abstract : Objective: To assess short- and long-term movement of renal arteries after fenestrated endovascular aortic repair (FEVAR). Methods: Consecutive patients who underwent FEVAR at one institution with a custom-made device designed with fenestrations for the superior mesenteric (SMA) and renal arteries, a millimetric computed tomography angiography (CTA), and a minimum of 2 years' follow-up were included. Angulation between renal artery trunk and aorta, clock position of the origin of the renal arteries, distance between renal arteries and SMA, and target vessel occlusion were retrospectively collected and compared between the pre-operative, post-operative (<6 months), and last (>12 months) CTA. Results: From October 2004 to January 2014, 100 patients met the inclusion criteria and 86% of imaging was available for accurate analysis. Median follow-up was 27.3 months (22.7–50.1). There were no renal occlusions. A significant change was found in the value of renal trunk angulation of both renal arteries on post-operative compared with pre-operative CTA (17° difference upward [7.5–29], p  < .001), but no significant change thereafter ( p  = .5). Regarding renal clock positions (7.5° of change equivalent to 15 min of renal ostial movement): significant anterior change was found between post-operative and pre-operative CTA (15 min [0–30], p  = .03 on the left and 15 min [15–30], p  < .001 on the right), without significant change thereafter (15 min [0–30], p  = .18 on the left and 15 min [0–15] on the right, p  = .28). No changes were noted on the distance between renal and SMA ostia (difference of 1.65 mm [1–2.5], p  = .63). Conclusion: The renal arteries demonstrate tolerance to permanent changes in angulation after FEVAR of approximately 17° upward trunk movement and of 15–30 min ostial movement without adverse consequences on patency after a median of more than 2 years' follow-up. The distance between the target vessels remained stable over time. These results may suggest accommodation to sizing errors and thus a compliance with off the shelf devices in favourable anatomies.